An Empirical study on the relationship between financial openness and economic growth - SHEN, Jun (KDI School, 2015)
By collecting the data of 102 countries over 1970-2009 periods, this paper employs a two-way fixed effects panel data model to study the relationship between financial openness and economic growth. Notice that differences not only exist between developed countriesand developing countries, but also within the developing countries, we divide the sample countries into three types which are developed countries, emerging market countries and developing countries for this study. Therefore, this paper analysesthe impact of financial openness on economic growth from the perspectives of both overallsamples and distinguishing three types of nations which is different from the most present researches. By analyzingthe estimation results, we conclude that:(1) Financial openness plays a significant positive role in promoting economic growth generally, which varies from different capital types. The impact of FDI inflow is the most obvious one, while there is not any significant positive impact on this three nation types exerted by debt capital inflow; (2) regarding the relationship between financial openness and economic growth, the emerging market economics varies greatly from developed countries and developing countries. Generally, the significant positive promotion impact is mainly from emerging market countries. Finally, the implication for China’s financial openness is that China should promote economic reform by promoting financial openness, because financial openness is the premise, the foundation and the assurance of reform.
Thesis(Master) --KDI School:Master of Public Policy,2015